Study on failure mechanism of deep soft rock roadway and high prestress compensation support countermeasure. (January 2023) - Sun, X.M.; Zhao, W.C.; Shen, F.X.; Zhang, Y.; Jiang, M.
Abstract: The problem of surrounding rock stability control of deep soft rock has become increasingly prominent. Taking Shiyakou Coal Mine as the engineering background, the deformation and failure characteristics of roadway is obtained through on-site investigation and drilling peep. X-ray diffraction and electron microscope scanning experiments analyze the mineral composition and microstructure of surrounding rock, and the microscopic mechanism of roadway failure is obtained. The relationship between roadway deformation, rock inclination and position of the weak layer was analyzed by the numerical simulation. And the deformation and failure mechanism of soft rock cross-cut roadway is obtained. By analyzing the action mechanism of the high-stress compensation support theory, the countermeasure of high prestress es compensation support based on Constant-resistance large deformation (CRLD) bolt was put forward. The analysis of field test and monitoring results show that the control effect of the new support scheme is good and has guiding for similar projects.